A spinal fusion cage based on piezoelectric bone core structure and a drug sustained-release preparation method thereof

CN122955030APending Publication Date: 2026-10-23KUNSHAN FIRST PEOPLES HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611233151.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0011]鉴于上述和/或现有的一种基于压电骨核结构的脊柱融合器及其药物缓释制备方法中存在的现有脊柱融合器中压电材料生物安全性差、压电响应弱以及药物释放周期短、存在突释效应的问题,提供一种兼具高灵敏度、高生物安全性及长效智能缓释功能的压电骨核脊柱融合器问题,因此,提出了本发明

Benefits of technology

1. 高安全性(解决毒性):SiO2惰性壳层和PVDF-TrFE基体的双重包覆,彻底阻断了Ba²⁺的溶出,使得高活性的BaTiO3可以安全用于终身植入。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a kind of based on piezoelectric bone core structure's spinal fusion cage and its drug sustained-release preparation method, it is related to medical instrument technical field, from inside to outside include successively: bottom layer: 3D printing porous support matrix, the matrix has the pore structure for mechanical support and bone long in;Intermediate layer: the core-shell structure piezoelectric composite coating arranged on the outer surface of the bottom layer, the piezoelectric composite coating includes piezoelectric polymer matrix and the core-shell structure nanoparticles dispersed in it, the core-shell structure nanoparticles are made of dielectric ceramic core and the insulating shell layer coated on the surface of the core body.Confirmed that the high safety (solves toxicity) of the application: the double coating of SiO2 inert shell layer and PVDF-TrFE matrix, the dissolution of Ba²⁺ is completely blocked, so that high activity BaTiO3 can be safely used for lifelong implantation, using the high d_{33} value of BaTiO3, compared with pure PVDF material, stronger electric signal can be generated, more effectively simulate the natural piezoelectricity of bone, promote osteoblast differentiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical device technology, and in particular to a spinal fusion device based on a piezoelectric bone core structure and its drug sustained-release preparation method. Background Technology

[0002] Spinal fusion is the gold standard for treating conditions such as intervertebral disc degeneration and spinal instability. Currently, commonly used fusion devices are mostly made of polyetheretherketone (PEEK) or titanium alloy (Ti6Al4V). To promote bone fusion, growth factors such as bone morphogenetic protein-2 (BMP-2) are usually filled into the fusion device.

[0003] In existing technologies, researchers have attempted to introduce piezoelectric materials (such as barium titanate BaTiO3 and polyvinylidene fluoride PVDF) to endow implants with bioactivity.

[0004] 1. Inorganic piezoelectric ceramics (such as BaTiO3): have extremely high piezoelectric coefficients (d33≈190 pC / N) and can generate strong electrical signals to stimulate osteoogenesis. However, as a lifelong implant, there is a risk of barium ion (Ba²⁺) dissolution in the body's physiological environment (especially the slightly acidic environment caused by inflammation), which has potential cytotoxicity.

[0005] 2. Organic piezoelectric polymers (such as PVDF): They have good biocompatibility, but their piezoelectric coefficient is low (d d33≈20-30pC / N), resulting in weak electrical signals that are difficult to effectively induce deep bone tissue regeneration.

[0006] 3. Drug release control: Most current drug-loaded fusion devices use physical adsorption, which has a "burst release effect," meaning that a large amount of drug is released in the early stages of implantation. This not only causes waste but may also cause side effects such as heterotopic ossification, making it difficult to maintain an effective therapeutic concentration for up to six months.

[0007] The existing technology has the following main shortcomings: 1. Insufficient biocompatibility: Simply using BaTiO3 nanoparticles as a lifelong implant material cannot completely block the long-term leaching risk of heavy metal ions.

[0008] 2. The contradiction between piezoelectric properties and biocompatibility: Highly sensitive inorganic materials are toxic, while safe organic materials have low sensitivity, making it difficult to achieve both.

[0009] 3. Uncontrollable drug release: There is a lack of a mechanism that can respond to the spinal microenvironment (such as micromotion) and maintain a long-term (more than six months) stable release of BMP-2. Summary of the Invention

[0010] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0011] In view of the problems existing in the above and / or existing spinal fusion devices based on piezoelectric core structures and their drug sustained-release preparation methods, such as poor biosafety of piezoelectric materials, weak piezoelectric response, short drug release cycle, and burst release effect, this invention is proposed to provide a piezoelectric core spinal fusion device that combines high sensitivity, high biosafety, and long-acting intelligent sustained-release function.

[0012] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a spinal fusion device based on a piezoelectric bone core structure, comprising, from the inside out: Bottom layer: 3D printed porous support matrix, which has a porous structure for mechanical support and bone ingrowth; Intermediate layer: A core-shell piezoelectric composite coating disposed on the outer surface of the bottom layer. The piezoelectric composite coating includes a piezoelectric polymer matrix and core-shell nanoparticles dispersed therein. The core-shell nanoparticles are composed of a dielectric ceramic core and an insulating shell covering the surface of the core. The piezoelectric composite coating is subjected to high-voltage polarization treatment and has a piezoelectric effect, which is used to convert the micro-motion mechanical energy of the spine into electric field energy. Surface layer: A smart drug-loaded hydrogel layer disposed on the outer surface of the intermediate layer. The hydrogel layer is loaded with bone morphogenetic proteins. The bone morphogenetic proteins are adsorbed into the hydrogel network by electrostatic interaction. The hydrogel layer changes its swelling state or disrupts its electrostatic balance in response to changes in the electric field generated by the intermediate layer, so as to achieve controlled release of the drug.

[0013] It should be noted that the material of the 3D printed porous support matrix is ​​medical-grade titanium alloy Ti6Al4V or polyetheretherketone (PEEK), and the porosity of the pore structure is 60%-80%.

[0014] Furthermore, the piezoelectric polymer matrix is ​​a polyvinylidene fluoride-trifluoroethylene copolymer PVDF-TrFE; The dielectric ceramic core is barium titanate BaTiO3 nanoparticles. The insulating shell is a silicon dioxide (SiO2) shell, which is coated on the surface of the BaTiO3 nanoparticles by a sol-gel method, and its thickness is 5-20 nm.

[0015] It should be noted that the high-voltage polarization treatment is a corona polarization treatment, which causes the PVDF-TrFE matrix to form a β-crystal phase, and the BaTiO3 nanoparticles are aligned in the same direction along the polarization electric field to maximize the piezoelectric response.

[0016] Furthermore, the smart drug-carrying hydrogel layer is a modified hyaluronic acid / chitosan composite hydrogel; The bone morphogenetic protein is BMP-2, whose isoelectric point is higher than that of the hydrogel network, causing the BMP-2 molecules to carry a positive charge and be adsorbed into the negatively charged hydrogel network through electrostatic attraction.

[0017] It should be noted that the mechanism by which the hydrogel layer releases the drug in response to changes in the electric field is as follows: the micro-electric field generated by the intermediate layer changes the ion distribution and network charge density within the hydrogel, weakens the electrostatic adsorption force between the hydrogel network and BMP-2 molecules, and / or causes changes in the swelling degree of the hydrogel, thereby inducing the release of BMP-2 from the hydrogel network.

[0018] It should be noted that an interface bonding layer is provided between the intermediate layer and the surface layer. The interface bonding layer is a PVDF-TrFE surface layer that has been activated by oxygen plasma and modified with a silane coupling agent, which is used to enhance the interfacial bonding strength between the piezoelectric composite coating and the hydrogel layer.

[0019] A method for fabricating a spinal fusion device based on a piezoelectric bone core structure includes the following steps: Step 1: Prepare core-shell structured nanoparticles by coating the surface of dielectric ceramic nanoparticles with an insulating shell using the sol-gel method to obtain core-shell structured nanoparticles. Step 2: Disperse the core-shell structured nanoparticles in a piezoelectric polymer solution, and coat them onto the surface of a 3D printed porous support substrate using a spraying or electrospinning process to form a composite coating. Then, subject the composite coating to high-voltage polarization treatment to obtain an intermediate layer with a piezoelectric effect. Step 3: Apply the hydrogel precursor liquid loaded with bone morphogenetic protein to the surface of the intermediate layer and perform in-situ cross-linking and curing to form a smart drug-loaded hydrogel surface layer, thus obtaining the spinal fusion device.

[0020] Furthermore, in step two, the high-voltage polarization treatment is a corona polarization treatment, with a polarization electric field strength of 80-120 MV / m, a polarization temperature of 60-100℃, and a polarization time of 20-60 min.

[0021] It should be noted that in step three, before applying the hydrogel precursor liquid, the polarized intermediate layer surface is first subjected to oxygen plasma activation treatment, then coated with a silane coupling agent for interface modification, and then the hydrogel is cross-linked and cured in situ.

[0022] Compared with the prior art, the present invention has the following outstanding advantages: 1. High safety (solving toxicity): The double coating of SiO2 inert shell and PVDF-TrFE matrix completely blocks the dissolution of Ba²⁺, making the highly active BaTiO3 safe for lifelong implantation.

[0023] 2. High sensitivity (positive piezoelectric effect): Utilizing the high d33 value of BaTiO3, it can generate a stronger electrical signal compared to pure PVDF materials, more effectively simulating the natural piezoelectricity of bone and promoting osteoblast differentiation.

[0024] 3. On-demand, long-lasting sustained release: Utilizing a "force-electricity-drug" coupling mechanism, the more the patient moves (the greater the spinal micro-movement), the stronger the generated electrical signal, and the faster the drug is released, achieving "on-demand treatment." The hydrogel matrix effectively avoids burst release and can maintain stable release for up to 6 months. Attached Figure Description

[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is a cross-sectional view of the overall structure of a spinal fusion device based on a piezoelectric bone core structure and its drug sustained-release preparation method.

[0027] Figure 2 This is a schematic diagram of the microstructure of the intermediate layer "piezoelectric core" in a spinal fusion device based on a piezoelectric core structure and its drug sustained-release preparation method.

[0028] Figure 3 This is a schematic diagram illustrating the drug release principle of a spinal fusion device based on a piezoelectric bone core structure and its drug release preparation method. Detailed Implementation

[0029] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.

[0030] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0032] refer to Figures 1-3 A spinal fusion device based on a piezoelectric bone core structure, comprising, from the inside out: Bottom layer: 3D printed porous support matrix with a porous structure for mechanical support and bone ingrowth; Intermediate layer: A core-shell piezoelectric composite coating is disposed on the outer surface of the bottom layer. The piezoelectric composite coating includes a piezoelectric polymer matrix and core-shell nanoparticles dispersed therein. The core-shell nanoparticles are composed of a dielectric ceramic core and an insulating shell covering the surface of the core. The piezoelectric composite coating is subjected to high voltage polarization treatment and has a piezoelectric effect, which is used to convert the micro-motion mechanical energy of the spine into electric field energy. Surface layer: A smart drug-loaded hydrogel layer located on the outer surface of the intermediate layer. This hydrogel layer is loaded with bone morphogenetic proteins, which are adsorbed onto the hydrogel network via electrostatic interactions. The hydrogel layer responds to changes in the electric field generated by the intermediate layer, altering its swelling state or disrupting its electrostatic balance to achieve controlled drug release. Figure 1 The structure is shown in three layers: bottom layer (porous mesh), middle layer (dense coating), and top layer (hydrogel cover).

[0033] In this invention, the material of the 3D printed porous support matrix is ​​medical titanium alloy Ti6Al4V or polyether ether ketone (PEEK), and the porosity of the pore structure is 60%-80%.

[0034] The piezoelectric polymer matrix is ​​polyvinylidene fluoride-trifluoroethylene copolymer PVDF-TrFE. Figure 2 A magnified view shows the "core-shell structured particles" (BaTiO3 inside, wrapped with SiO2 on the outside) dispersed in the PVDF-TrFE matrix.

[0035] The dielectric ceramic core is composed of barium titanate (BaTiO3) nanoparticles; The insulating shell is a silicon dioxide (SiO2) shell, which is coated on the surface of BaTiO3 nanoparticles by a sol-gel method, and its thickness is 5-20 nm.

[0036] In this invention, the high-voltage polarization treatment is corona polarization treatment, which causes the PVDF-TrFE matrix to form a β-crystal phase, and the BaTiO3 nanoparticles are aligned in the same direction along the polarization electric field to maximize the piezoelectric response.

[0037] In this invention, the smart drug-loaded hydrogel layer is a modified hyaluronic acid / chitosan composite hydrogel; Bone morphogenetic protein BMP-2 has an isoelectric point higher than that of the hydrogel network, causing BMP-2 molecules to carry a positive charge and be adsorbed into the negatively charged hydrogel network through electrostatic attraction.

[0038] In this invention, the mechanism by which the hydrogel layer releases the drug in response to a change in electric field is as follows: the micro-electric field generated by the intermediate layer alters the ion distribution and network charge density within the hydrogel, weakening the electrostatic adsorption force between the hydrogel network and BMP-2 molecules, and / or causing a change in the swelling degree of the hydrogel, thereby inducing the release of BMP-2 from the hydrogel network. Figure 3 This demonstrates the process by which the piezoelectric layer generates charges during spinal micromovements, and the electric field acts on the release of BMP-2 molecules from the hydrogel.

[0039] In this invention, an interface bonding layer is provided between the intermediate layer and the surface layer. The interface bonding layer is a PVDF-TrFE surface layer that has been activated by oxygen plasma and modified with a silane coupling agent, which is used to enhance the interfacial bonding strength between the piezoelectric composite coating and the hydrogel layer.

[0040] A method for fabricating a spinal fusion device based on a piezoelectric bone core structure is as follows: Example 1: Preparation of SiO2@BaTiO3 core-shell nanoparticles This embodiment provides a method for preparing SiO2-coated BaTiO3 core-shell structured nanoparticles.

[0041] Step 1.1 Pretreatment of BaTiO3 nanoparticles BaTiO3 nanoparticles with an average particle size of 100~300nm were dispersed in anhydrous ethanol and ultrasonically dispersed for 15min. An appropriate amount of deionized water and ammonia were added to adjust the pH to alkaline (pH≈10). Ultrasonic dispersion was continued for 10min to form a uniform BaTiO3 suspension.

[0042] Step 1.2 SiO2 sol-gel coating Under stirring, an anhydrous ethanol solution of tetraethyl orthosilicate (TEOS) was added dropwise to the above BaTiO3 suspension, with a TEOS to BaTiO3 mass ratio of 1:5 to 1:20. The dropping rate was controlled at 0.5 mL / min, and the reaction was continuously stirred at room temperature for 6 to 12 h. TEOS hydrolyzed and condensed under alkaline conditions, forming a SiO2 shell in situ on the surface of the BaTiO3 particles.

[0043] Step 1.3 Post-processing After the reaction was completed, the product was centrifuged and washed three times with anhydrous ethanol and deionized water, then dried under vacuum at 60℃ for 12 h, and then calcined at 500℃ for 2 h to obtain SiO2@BaTiO3 core-shell structured nanoparticles. Transmission electron microscopy images showed that the SiO2 shell thickness was 5~20 nm, and the coating was complete, uniform and dense.

[0044] Example 2: Preparation and polarization of PVDF-TrFE / SiO2@BaTiO3 composite piezoelectric coating This embodiment provides a method for constructing and polarizing a core-shell structure piezoelectric composite coating on the surface of a 3D-printed porous substrate.

[0045] Step 2.1 Preparation of composite slurry The SiO2@BaTiO3 core-shell nanoparticles prepared in Example 1 were added at a mass fraction of 10%~30% to a PVDF-TrFE (molar ratio 70:30) mixed solution of N,N-dimethylformamide (DMF) / acetone (volume ratio 7:3), where the mass concentration of PVDF-TrFE was 8%~15%. An appropriate amount of dispersant was added, and the mixture was magnetically stirred for 24 hours and ultrasonically degassed for 30 minutes to obtain a uniformly dispersed composite slurry.

[0046] Step 2.2 Coating Preparation A porous support matrix of Ti6Al4V or PEEK was pre-prepared using 3D printing technology. The composite slurry was then uniformly coated onto the outer surface of the porous matrix using an air spraying method, with the coating thickness controlled between 50 and 200 μm. After spraying, the matrix was dried in a vacuum oven at 60°C for 12 hours to remove residual solvent.

[0047] Step 2.3 High-voltage corona polarization treatment The substrate coated with the composite coating was placed in a corona polarization apparatus for high-voltage polarization treatment. Polarization conditions: polarization electric field strength 80–120 MV / m, polarization temperature 80–100℃ (above the Curie temperature of PVDF-TrFE), and polarization time 30–60 min. After polarization treatment, the electric field was maintained while cooling to room temperature to fix the β-crystal structure of the PVDF-TrFE substrate, while ensuring consistent polarization orientation of the BaTiO3 particles.

[0048] Step 2.4 Piezoelectric Performance Verification The polarized composite coating adopts quasi-static d 33 The tester measures the piezoelectric coefficient, d 33 The value reached 50~80 pC / N, which is significantly higher than the 20~30 pC / N of the pure PVDF-TrFE coating, proving that the BaTiO3 core-shell particles have a significant enhancing effect on piezoelectric properties.

[0049] Example 3: Preparation of the surface layer of the smart drug-loaded hydrogel This embodiment provides a method for in-situ crosslinking of BMP-2-loaded modified hyaluronic acid / chitosan composite hydrogels on the surface of a piezoelectric coating.

[0050] Step 3.1 Preparation of hydrogel precursor solution Methacrylic anhydride-modified hyaluronic acid (MeHA) and chitosan (CS) were dissolved in phosphate-buffered saline (PBS, pH=7.4) at a mass ratio of 3:1 to 5:1, resulting in a total polymer concentration of 2% to 5%. Irgacure 2959 (0.1% to 0.5% by mass) was added as a photoinitiator and stirred until completely dissolved. Bone morphogenetic protein-2 (BMP-2) solution was added to the above precursor solution, resulting in a final BMP-2 concentration of 50 to 200 μg / mL. The mixture was gently stirred under ice bath conditions to ensure uniform dispersion. Under these conditions, BMP-2 molecules (isoelectric point pI≈8.5, positively charged at pH=7.4) adsorbed onto the chitosan and hyaluronic acid molecular chains via electrostatic interactions.

[0051] Step 3.2 Interface Integration Layer Processing (Preferred) As a preferred embodiment, before applying the hydrogel coating, the surface of the polarized intermediate layer is first subjected to oxygen plasma activation treatment (power 50W, treatment time 2~5min), and then a silane coupling agent (such as KH-550) is applied for interface modification to enhance the interfacial bonding strength between the piezoelectric layer and the hydrogel layer.

[0052] Step 3.3 In-situ photocrosslinking to form a gel The BMP-2-containing hydrogel precursor solution obtained in step 3.1 was dropped or sprayed onto the surface of the piezoelectric composite coating after interface treatment, and allowed to stand for 5 minutes to allow the precursor solution to fully wet and spread. Ultraviolet light with a wavelength of 365 nm (intensity 5~10 mW / cm²) was then applied for 30~60 s to initiate a photocrosslinking reaction between MeHA molecular chains, forming a three-dimensional network structure hydrogel layer. The thickness of the hydrogel layer was controlled at 100~300 μm.

[0053] Step 3.4 Post-processing The drug-loaded hydrogel coating was immersed and washed three times in PBS buffer to remove unreacted monomers and unloaded free BMP-2, thus obtaining the finished product of the intelligent sustained-release spinal fusion device with a piezoelectric bone core structure.

[0054] Example 4: Verification of the sustained-release performance of "mechanical-electrical-pharmaceutical" coupling This embodiment characterizes the drug release behavior of the spinal fusion device prepared in this invention under simulated spinal micromotion conditions.

[0055] Step 4.1 In vitro simulated micro-release test The drug-loaded fusion device sample prepared in Example 3 was placed in a dynamic mechanical loading device and immersed in PBS release medium (pH=7.4, 37℃). Loading conditions: frequency 1Hz (simulating normal gait frequency), compressive load 50~200N, simulating physiological micro-movements of spinal segments. The control group consisted of the same batch of samples immersed in PBS under unloaded conditions.

[0056] Step 4.2 Release kinetic analysis Samples were taken at preset time points (1h, 6h, 12h, 1d, 3d, 7d, 14d, 28d, 60d, 90d, 120d, 180d), and the concentration of BMP-2 in the release medium was determined by ELISA. The cumulative release curve was plotted.

[0057] Step 4.3 Results Analysis Release kinetics results show that: (1) No burst release effect. Unlike the "initial burst release" (release >40% within 24h) of the physical adsorption drug loading control group, the cumulative release of the hydrogel group of the present invention is <10% within 24h, and BMP-2 is effectively anchored by the hydrogel network.

[0058] (2) On-demand release characteristics: The cumulative release rate of BMP-2 in the loaded group was significantly higher than that in the unloaded group. Under loading conditions, the piezoelectric coating converts cyclic compressive mechanical energy into a micro-electric field. This electric field alters the swelling state of the hydrogel network and / or weakens the electrostatic binding force between BMP-2 and the polymer chains, thereby triggering drug release. The greater the load (the greater the simulated activity), the higher the intensity of the generated micro-electric field and the faster the release rate.

[0059] (3) Long-term stability: The release curve shows that under loading conditions, BMP-2 can maintain a continuous and stable release concentration (cumulative release of 60%~80%) within 180 days (6 months), which meets the complete bone healing cycle required for spinal fusion.

[0060] Example 5: Evaluation of biocompatibility and in vitro osteogenic activity Step 5.1 Cytotoxicity Evaluation Following ISO 10993-5 standards, the CCK-8 assay was used to evaluate the effect of the extract from the fusion vessel sample on the activity of MC3T3-E1 mouse osteoblast precursor cells. The results showed that after culturing the extract for 24, 48, and 72 hours, the relative cell growth rate (RGR) was consistently >90%, and the cytotoxicity grade was 0 or 1, demonstrating that the effective coating of the SiO2 shell on the BaTiO3 core completely blocked the dissolution of Ba²⁺, and the material exhibited no significant cytotoxicity.

[0061] Step 5.2 Evaluation of osteogenic differentiation induction MC3T3-E1 cells were seeded onto the sample surface and cultured in osteogenic induction medium for 7 and 14 days. Results showed that, compared to the pure PEEK / Ti6Al4V control group, the piezoelectric active fusion device group of this invention significantly upregulated alkaline phosphatase (ALP) activity, and the expression levels of osteogenic-related genes such as Runx2 and osteocalcin (OCN) were increased by 2–4 times. This difference was even more significant under dynamic mechanical loading conditions, confirming the positive regulatory effect of piezoelectric signals on osteogenic differentiation.

[0062] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A spinal fusion device based on a piezoelectric bone core structure, characterized in that, From the inside out, the following are included: Bottom layer: 3D printed porous support matrix, which has a porous structure for mechanical support and bone ingrowth; Intermediate layer: A core-shell piezoelectric composite coating disposed on the outer surface of the bottom layer. The piezoelectric composite coating includes a piezoelectric polymer matrix and core-shell nanoparticles dispersed therein. The core-shell nanoparticles are composed of a dielectric ceramic core and an insulating shell covering the surface of the core. The piezoelectric composite coating is subjected to high-voltage polarization treatment and has a piezoelectric effect, which is used to convert the micro-motion mechanical energy of the spine into electric field energy. Surface layer: A smart drug-loaded hydrogel layer disposed on the outer surface of the intermediate layer. The hydrogel layer is loaded with bone morphogenetic proteins. The bone morphogenetic proteins are adsorbed into the hydrogel network by electrostatic interaction. The hydrogel layer changes its swelling state or disrupts its electrostatic balance in response to changes in the electric field generated by the intermediate layer, so as to achieve controlled release of the drug.

2. The spinal fusion device based on a piezoelectric bone core structure according to claim 1, characterized in that: The 3D printed porous support matrix is ​​made of medical-grade titanium alloy Ti6Al4V or polyether ether ketone (PEEK), and the porosity of the pore structure is 60%-80%.

3. The spinal fusion device based on a piezoelectric bone core structure according to claim 1, characterized in that: The piezoelectric polymer matrix is ​​a polyvinylidene fluoride-trifluoroethylene copolymer PVDF-TrFE; The dielectric ceramic core is barium titanate BaTiO3 nanoparticles. The insulating shell is a silicon dioxide (SiO2) shell, which is coated on the surface of the BaTiO3 nanoparticles by a sol-gel method, and its thickness is 5-20 nm.

4. The spinal fusion device based on a piezoelectric bone core structure according to claim 1, characterized in that: The high-voltage polarization treatment is a corona polarization treatment, which causes the PVDF-TrFE matrix to form a β-crystal phase, and the BaTiO3 nanoparticles to be aligned in the direction of the polarization electric field in order to maximize the piezoelectric response.

5. The spinal fusion device based on a piezoelectric bone core structure according to claim 1, characterized in that: The intelligent drug-carrying hydrogel layer is a modified hyaluronic acid / chitosan composite hydrogel. The bone morphogenetic protein is BMP-2, whose isoelectric point is higher than that of the hydrogel network, causing the BMP-2 molecules to carry a positive charge and be adsorbed into the negatively charged hydrogel network through electrostatic attraction.

6. The spinal fusion device based on a piezoelectric bone core structure according to claim 1, characterized in that: The mechanism by which the hydrogel layer releases the drug in response to changes in the electric field is as follows: the micro-electric field generated by the intermediate layer changes the ion distribution and network charge density within the hydrogel, weakens the electrostatic adsorption force between the hydrogel network and BMP-2 molecules, and / or causes changes in the swelling degree of the hydrogel, thereby inducing the release of BMP-2 from the hydrogel network.

7. The spinal fusion device based on a piezoelectric bone core structure according to any one of claims 1 to 6, characterized in that: An interface bonding layer is further provided between the intermediate layer and the surface layer. The interface bonding layer is a PVDF-TrFE surface layer that has been activated by oxygen plasma and modified with a silane coupling agent, which is used to enhance the interfacial bonding strength between the piezoelectric composite coating and the hydrogel layer.

8. A method for fabricating a spinal fusion device based on a piezoelectric bone core structure as described in any one of claims 1 to 7, characterized in that, Includes the following steps: Step 1: Prepare core-shell structured nanoparticles by coating the surface of dielectric ceramic nanoparticles with an insulating shell using the sol-gel method to obtain core-shell structured nanoparticles. Step 2: Disperse the core-shell structured nanoparticles in a piezoelectric polymer solution, and coat them onto the surface of a 3D printed porous support substrate using a spraying or electrospinning process to form a composite coating. Then, subject the composite coating to high-voltage polarization treatment to obtain an intermediate layer with a piezoelectric effect. Step 3: Apply the hydrogel precursor liquid loaded with bone morphogenetic protein to the surface of the intermediate layer and perform in-situ cross-linking and curing to form a smart drug-loaded hydrogel surface layer, thus obtaining the spinal fusion device.

9. The preparation method according to claim 8, characterized in that: In step two, the high-voltage polarization treatment is a corona polarization treatment, with a polarization electric field strength of 80-120 MV / m, a polarization temperature of 60-100℃, and a polarization time of 20-60 min.

10. The preparation method according to claim 8, characterized in that: In step three, before applying the hydrogel precursor liquid, the polarized intermediate layer surface is first subjected to oxygen plasma activation treatment, then coated with a silane coupling agent for interface modification, and then the hydrogel is cross-linked and cured in situ.